2013
DOI: 10.1111/pan.12107
|View full text |Cite
|
Sign up to set email alerts
|

Procedural pain in neonates: the state of the art in the implementation of national guidelines in Italy

Abstract: This survey showed that most Italian NICUs provide some form of analgesia and sedation for invasive procedures in accordance with national guidelines, but their routine adherence to best practices for pain control and monitoring is still suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
5
23
0
6
Order By: Relevance
“…Similarly, the routine use of medication for major invasive procedures was still limited (35 % of lumbar punctures, 40 % of tracheal intubations, 46 % during mechanical ventilation), and postoperative pain treatment was also inadequate. Consequently, the authors concluded that despite the improvements in neonatal analgesia practices in Italy since national guidelines were published, pain is still largely undertreated and underscored [14,19].…”
Section: Why Do Neonates Need Procedural Analgo-sedation?mentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, the routine use of medication for major invasive procedures was still limited (35 % of lumbar punctures, 40 % of tracheal intubations, 46 % during mechanical ventilation), and postoperative pain treatment was also inadequate. Consequently, the authors concluded that despite the improvements in neonatal analgesia practices in Italy since national guidelines were published, pain is still largely undertreated and underscored [14,19].…”
Section: Why Do Neonates Need Procedural Analgo-sedation?mentioning
confidence: 95%
“…The increased awareness that neonates feel pain, the ethical obligation to treat this pain with analgesics, the growing body of evidence demonstrating that untreated neonatal pain can lead to altered reactivity to pain that persists throughout infancy and childhood, as well as the need for a humane management of neonates resulted in the development of guidelines to promote the use of analgesics in neonates [3,14]. The main objectives of sedation and analgesia are reduction of pain, stress and irritability, and promotion of physiological stability.…”
Section: Why Do Neonates Need Procedural Analgo-sedation?mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other studies 5,7,13,16 also highlighted deficiencies in the use of sedatives and analgesics in neonatal units.…”
Section: 4mentioning
confidence: 99%
“…Within this concept and to adequately act in face of potential painful situations, in addition to knowing that NBs express pain, it is important to have tools to "decode" this language. Even with major advances, the literature still has a gap between scientific knowledge of the subject and its consequences and the use of methods to evaluate and manage pain 1 . Pain stimulation and perception are present before birth.…”
Section: Introductionmentioning
confidence: 99%